Investigating Factors Associated with Thymic Regeneration after Chemotherapy in Patients with Lymphoma - Sun, Dao-Ping; Wang, Li; Ding, Chong-Yang; Liang, Jin-Hua; Zhu, Hua-Yuan; Wu, Yu-Jie; Fan, Lei; Li, Jian-Yong; Xu, Wei (Frontiers in Immunology, 2016)
The factors involved in thymus regeneration after chemotherapy has not been sufficiently explored. This study was aimed to identify the clinical characteristics and single-nucleotide polymorphisms (SNPs) in the gene (IL7R) encoding IL-7Rα associated with thymus renewal after chemotherapy in Chinese Han individuals with lymphoma. The dynamics of thymic activity in 134 adults with Hodgkin lymphoma (HL) and B cell lymphoma from baseline to 12 months post-chemotherapy were analyzed by assessing thymic structural changes using serial computed tomography scans, and correlating these with measurements of thymic output by concurrent analysis of single-joint T-cell receptor excision circles (sjTREC) and CD31+ recent thymic emigrants (RTE) in peripheral blood. The association of clinical variables and IL7R polymorphisms with the occurrence of rebound thymic hyperplasia (TH) and the recovery of thymic output following chemotherapy was evaluated. Thymic regeneration was observed, with the evidence that TH occurred in 38/134 (28.4%) cases, and thymic output, assessed by CD31+ RTE numbers and sjTREC content, recovered to baseline levels within one year after the end of therapy. The frequencies of the T allele and TT + GT genotype of rs7718919 located in the promoter of IL7R were significantly higher in patients with TH compared with those without TH (P=0.031 and 0.027, respectively). In contrast, no significant difference was found between two groups with respect to the distribution of allele and genotype frequencies of rs6897932. By general linear models repeated-measure analysis, rs7718919 and rs6897932 were determined to exert no significant effects on the recovery of thymic output after therapy. Univariate analysis revealed host age under 30, the diagnosis of HL, baseline thymic index and CD31+ RTE counts, and rs7718919 genotype as potential predictors for TH after chemotherapy (P<0.05); after multivariate adjustment, only host age was independently associated with the occurrence of TH (OR=4.710, 95%CI: 1.727–12.845, P=0.002). These findings indicate that patient age is an independent predictor for thymic regrowth after chemotherapy, which should promote awareness among physicians to make a timely diagnosis of TH in young adults, and help physicians to prioritize intervention strategies for thymus rejuvenation in this population.